Body Tracking Technologies for Ergonomic Evaluation - Martinsson, Jacob; Svensjö, Joel (My University, 2026)
Ergonomic evaluations at Volvo Trucks Tuve are currently performed manually using an internal video-based assessment method, which is time-consuming and difficult to scale across a large number of workstations. This thesis evaluated whether currently available body tracking systems, with a focus on markerless solutions, can support ergonomic assessment in truck assembly. The study combined technical evaluation with socio-technical analysis by considering posture detection capability, evaluation time, workflow compatibility, transparency, data handling, and user acceptance. The investigated systems showed potential to reduce parts of the manual analysis workload and provide quantitative posture data, but their performance and practical usefulness varied between systems, body regions, and recording conditions. The results also showed that successful implementation depends on more than technical accuracy, as the systems must fit existing work practices and be trusted by users. Occurrence Ergo was selected as the most suitable candidate for further evaluation. Overall, body tracking technologies show potential as decision-support tools, but should not currently be regarded as fully autonomous ergonomic assessment systems
Keywords: Body tracking; motion capture; ergonomic evaluation; markerless motion capture; truck assembly